Investigation of the 4D composite MR image distortion field associated with tumor motion for MR‐guided radiotherapy. Issue 3 (1st March 2016) - Stanescu, T.; Jaffray, D.
Abstract : Purpose: Magnetic resonance (MR) images are affected by geometric distortions due to the specifics of the MR scanner and patient anatomy. Quantifying the distortions associated with mobile tumors is particularly challenging due to real anatomical changes in the tumor's volume, shape, and relative location within the MR imaging volume. In this study, the authors investigate the 4D composite distortion field, which combines the effects of the susceptibility‐induced and system‐related distortion fields, experienced by mobile lung tumors. Methods: The susceptibility ( χ ) effects were numerically simulated for two specific scenarios: (a) a full motion cycle of a lung tumor due to breathing as depicted on ten phases of a 4D CBCT data set and (b) varying the tumor size and location in lung tissue via a synthetically generated sphere with variable diameter (4–80 mm). The χ simulation procedure relied on the segmentation and generation of 3D susceptibility ( χ ) masks and computation of the magnetic field by means of finite difference methods. A system‐related distortion field, determined with a phantom and image processing algorithm, was used as a reference. The 4D composite distortion field was generated as the vector summation of the χ ‐induced and system‐related fields. The analysis was performed for two orientations of the main magnetic field ( B 0 ), which correspond to several MRIgRT system configurations. Specifically, B 0 was set along the z ‐axis as in the case of a cylindrical‐bore scanner and in the ( x, y )‐plane as for a biplanar MR. Computations were also performed for a full revolution at 15° increments in the case of a rotating biplanar magnet. Histograms and metrics such as maximum, mean, and range were used to evaluate the characteristics of the 4D distortion field. Results: The χ ‐induced field depends on the change in volume and shape of the moving tumor as well as the local surrounding anatomy. In the case of system‐related distortions, the tumor experiences increased field perturbations as it moves further away from the MR isocenter. For a mobile lung tumor, the 4D composite field, corresponding to a 1.5 T field and a readout gradient of 5 mT/m, amounts to 3.0 and 2.8 mm for the MRIgRT system designs featuring B 0 oriented along the z ‐axis (cylindrical‐bore scanner) and in the ( x, y )‐plane (biplanar scanner), respectively. For a rotating biplanar scanner, the composite distortion field varied nonlinearly with the rotation angle. Overall, the dominant contribution to the composite field was from the system‐related distortion field. The tumor centroid experienced a systematic shift of 2 mm and showed a negligible perturbation for different B 0 values. The dependency on the tumor size was also investigated, namely the max values varied from 1.2 to 2.5 mm for spherical volumes with a diameter between 4 and 80 mm. Conclusions: The composite distortion field requires adequate quantification for lung radiation therapy applications such as treatment planning, pretreatment patient setup verification, and real‐time treatment delivery guidance. For certain scenarios such as small tumor volumes, the spatial distortions may be corrected by applying systematic shifts derived from a single tumor motion phase. In the case of high readout gradients common to fast imaging applications, the χ distortions were found to be less than 1 mm irrespective of scanner configuration.